Outcome of Iron Deficiency Anemia in patients presenting with Breath Holding Spellsat Lady Reading Hospital Peshawar - Muhammad Abbas, Bakht Muhammad, Amjad Ali, Wasimullah, Mujtaba Gul, Abid Malook (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To ascertain the course of iron deficiency anemia in patients who presented to OPD and wards with breath-holding episodes. Methodology: From June 19 through December 18, 2019, the pediatrics department of Lady Reading Hospital in Peshawar conducted this study with ethical committee approval. The study included all kids aged 1 to 5 years, both genders, and those who had Cyanotic Breath spell lasting two or more episodes. Children with Cyanotic congenital heart disease, a history of febrile convulsions or epilepsy, anticonvulsive therapy currently being used, delayed children, and malnutrition in the past were not included in the study. Results: In our 161 patients, the average age was 2.671.811, the average weight was 12.913.33kg, and the average length of illness was 6.834.24 months. Males made up 94(58.4%) and females 67 (41.6%) of the patient population, while PICA children made up 72(44.7%). Iron deficiency anemia was present in 87(54%) of the patient population, but not in 74(46%), who had it. PICA children and children who were breastfed exclusively had a significantly higher correlation with iron deficient anemia. Conclusion: It is highly typical for patients who experience breath holding spells to have iron deficient anemia. These patients should receive an accurate diagnosis of iron deficiency anemia and treatment to soothe the parents’ concerns and limit the frequency of unneeded hospital visits. Key words: iron deficiency anemia, breath holding spells, PICA child